Validity of Field Methods to Estimate Fat-Free Mass Changes Throughout the Season in Elite Youth Soccer Players - Núñez, F. Javier; Munguía-Izquierdo, Diego; Suárez-Arrones, Luis (Frontiers in Physiology, 2020)
The aim of this study was to determine the most effective anthropometric equations or BIA devices for quantifying the sensitivity to change in fat free mass (FFM) in elite young soccer players, in comparison with measurement using dual-energy X-ray absorptiometry (DXA), between pre-season and mid-season. A total of 40 elite youth soccer players participated in this study. DXA values provided a criterion measure of FFM. Correlation coefficients, biases, limits of agreement, and differences were used as measures of sensitivity to change. All body density, skinfold, and anthropometric equations and BIA devices used to obtain FFM data showed positive and very large correlations (r from 0.70 to 0.89) with DXA. A significant increase in FFM was shown between time points using DXA, bioelectrical impedance analysis (BIA) and all anthropometric equations (p<0.01). The magnitudes of differences were small for DXA, BIA Inbody and all anthropometric equations except those of Faulkner et al. (1966), Durnin & Rahaman (1967), Brook (1971) and Sarria et al. (1998). Six anthropometric equations (Slaughter et al. (1988), Faulkner et al. (1966), Carter et al. (1982), Durnin & Womersley (1974), Reilly et al. (2009), and Munguia-Izquierdo et al. (2018)) and BIA Tanita showed no statistical differences compared to DXA, with a low bias. We concluded that the equations developed by Slaughter et al.(1988), Carter et al.(1982)(1), Durnin & Womersley(1974), Reilly et al. (2009), and Munguia-Izquierdo et al. (2018) showed the best sensitivity in assessing FFM changes between pre-season and mid-season in elite youth soccer players.